PENGELOLAAN KEUANGAN TERKOMPUTERISASI DI FAKULTAS ILMU KOMPUTER UNIVERSITAS SRIWIJAYA MENGGUNAKAN SISTEM ENTERPRISE RESOURCE PLANNING (ERP) - Hadipurnawan Satria; Anggina Primanita; M. Nazhif Rizani; Hasby Rifky; Ahmad Nizar (Annual Research Seminar (ARS), 2016)
A university faculty has numerous and complex business processes that it can be assumed as a corporation. Implementing an Enterprise Resource Planning (ERP) system in a faculty has to integrate all the elements in a faculty, such as departments and other units. Integrated system will ease the monitoring and evaluation process in a faculty. This research analyzes the requirements needed to integrate between faculty and university finance system at Computer Science Faculty, Sriwijaya University. The result of requirement analysis is then represented in UML Diagrams and implemented in Web platform. Based on the implementation results, all of the requirements has been implemented accordingly. It is expected to streamlined the finance processes in Computer Science Faculty, as well as creating a more accountable and transparent financial environment.